Adaptation of the Human Gut Microbiota Metabolic Network During the First Year After Birth - Fuertes, Alvaro; Pérez-Burillo, Sergio; Apaolaza, Iñigo; Vallès, Yvonne; Francino, M. Pilar; Rufián-Henares, José Ángel; Planes, Francisco J. (Frontiers in Microbiology, 2019)
Predicting the metabolic behavior of the human gut microbiota in different contexts is one of the most promising areas of constraint-based modeling. Recently, we presented a supra-organismal approach to build context-specific metabolic networks of bacterial communities using functional and taxonomic assignments of meta-omics data. In this work, this algorithm is applied to elucidate the metabolic changes induced over the first year after birth in the gut microbiota of a cohort of Spanish infants. We used metagenomics data of fecal samples and nutritional data of 13 infants at five time points. The resulting networks for each time point were analyzed, finding significant alterations once solid food is introduced in the diet. Our work shows that solid food leads to a different pattern of output metabolites that can be potentially released from the gut microbiota to the host. Experimental validation is presented for ferulate, a neuroprotective metabolite involved in the gut-brain axis.